2021
DOI: 10.3389/fbioe.2021.697310
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Catalyzed Copolymerization of Lignosulfonates for Hydrophobic Coatings

Abstract: Enzymatic polymerization of lignin can generate a variety of value-added products concomitantly replacing fossil-based resources. In line with this approach, a laccase from the thermophilic fungus Myceliophthora thermophila (MtL) was used to couple a hydrophobicity enhancing fluorophenol (FP) molecule, namely 4-[4-(trifluoromethyl)phenoxy]phenol (4,4-F3MPP), as a model substrate onto lignosulfonate (LS). During the coupling reaction changes in fluorescence, phenol content, viscosity and molecular weight (size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
(70 reference statements)
0
9
0
Order By: Relevance
“…The MWs were about 70 kDa in the case of lignosulfonate, as in our former study (Euring et al, 2016a), and about 20 kDa in the case of Indulin AT (Table 1). Mayr et al (2021) similarly reported a 30 min incubation time for Novozym 51003 incubated with lignosulfonate liquor for the best increase in MW, with a reduction in MW in subsequent incubation. In this study, also when the better mediator DMP was added to either the lignosulfonate or the Indulin AT in laccase solutions, a 30 min incubation time was required and also sufficient for the highest polymerization by all enzyme preparations, purified basi-laccase CcLcc5, unpurified CcLcc5, and asco-laccase MtL in Novozym 51003.…”
Section: Detection Of Mws Of Technical Lignins Via Gpc-effects Of Different Laccases and Mediatorsmentioning
confidence: 83%
See 1 more Smart Citation
“…The MWs were about 70 kDa in the case of lignosulfonate, as in our former study (Euring et al, 2016a), and about 20 kDa in the case of Indulin AT (Table 1). Mayr et al (2021) similarly reported a 30 min incubation time for Novozym 51003 incubated with lignosulfonate liquor for the best increase in MW, with a reduction in MW in subsequent incubation. In this study, also when the better mediator DMP was added to either the lignosulfonate or the Indulin AT in laccase solutions, a 30 min incubation time was required and also sufficient for the highest polymerization by all enzyme preparations, purified basi-laccase CcLcc5, unpurified CcLcc5, and asco-laccase MtL in Novozym 51003.…”
Section: Detection Of Mws Of Technical Lignins Via Gpc-effects Of Different Laccases and Mediatorsmentioning
confidence: 83%
“…For further comparison, the well-studied asco-laccase MtL has an optimal pH with syringaldazine as a phenolic substrate at pH 6.5 to 7.0 and with the non-phenolic ABTS at pH 2.7 (Berka et al, 1997;Xu, 1997) and the novel basi-laccase CcLcc5 at pH 7.0 and 5.0 (Rühl, 2010), indicating a good potential for enzymatic activities of CcLcc5 with substrates around the neutral pH. Indeed, pH values in the neutral range are best suited for laccase-catalyzed lignin polymerization reactions (Euring, 2008;Huber et al, 2016a;Ortner et al, 2018), among other things through a more open structure of lignosulfonates at pH 7.0 for better enzymatic access and for Indulin AT the restricted solubilization behavior at low pH (Huber et al, 2016a;Braunschmid et al, 2021;Mayr et al, 2021). These arguments together underline our investigation of the quality of basi-laccase CcLcc5 in experimental tests as an alternative to the asco-laccase MtL as functional enzymes in LLMS for MDF production.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction conditions for the enzymatic oxidation of LS were chosen as described in one of our previous studies [ 17 ]. Due to a lower pH suitable for the polymerization of LS a laccase originating from the thermophilic fungus Myceliophthora thermophila (MtL) [ 64 ] was used.…”
Section: Methodsmentioning
confidence: 99%
“…The third approach to upgrading lignin involves predominantly chemical modification, enzymatic modification has been described mainly for lignosulfonates (LS) and native lignin [ 12 , 13 , 14 ]. The resulting functional materials conveying antimicrobial or antioxidant activity can be used in adhesives, as graft co-polymers or in biomedical applications [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enzymes have been assessed to covalently incorporate hydrophobic molecules into lignins while fluorophenol molecules (FPs) were used as models, especially 4-[4-(trifluoromethyl)phenoxy]phenol (4,4-F3MPP). FPs have been successfully grafted on lignin model substrates [ 159 ] and lignocellulose fibers [ 160 , 161 ] and onto isolated lignosulfonates [ 150 ]. In the latest experiment, the water contact angle of the polymerized lignosulfonate with FP as an additive increased by 59.2% and the water swelling decreased by 216.8%, showing the ideality of the use of FPs as additives for improving the wet resistance.…”
Section: Techniques/processes For the Valorization Of Technical Ligninsmentioning
confidence: 99%